tìm x biết x4;x(-6) và -20 < x <-10
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có: f(x) + h(x) = g(x)
Suy ra: h(x) = g(x) – f(x) = (x4 – x3 + x2 + 5) – (x4 – 3x2 + x – 1)
= x4 – x3 + x2 + 5 – x4 + 3x2 – x + 1
= ( x4 – x4) – x3 + (x2 + 3x2 ) – x + (5+ 1)
= -x3 + 4x2 – x + 6
Ta có: f(x) – h(x) = g(x)
Suy ra: h(x) = f(x) – g(x) = (x4 – 3x2 + x – 1) – (x4 – x3 + x2 + 5)
= x4 – 3x2 + x – 1 – x4 + x3 – x2 – 5
= (x4 – x4) + x3 – (3x2 + x2) + x - (1+ 5)
= x3 – 4x2 + x – 6
Ta có: x 4 = 7 ⇔ x 2 2 = 7
⇔ x 2 = 7 ⇔ x 2 = 7
Vậy x = 7 và x = - 7
x4 + x = 55 , 35
x4 + x1 = 55 , 35
x x ( 1 + 4 ) = 55 , 35
x x 5 = 55 , 35
x = 55 , 35 : 5
x = 11 , 07
Đặt \(\sqrt{x^2+2012}=t>0\Rightarrow2012=t^2-x^2\)
Pt trở thành:
\(x^4+t=t^2-x^2\)
\(\Leftrightarrow x^4-t^2+x^2+t=0\)
\(\Leftrightarrow\left(x^2+t\right)\left(x^2-t+1\right)=0\)
\(\Leftrightarrow x^2+1=t\)
\(\Leftrightarrow x^2+1=\sqrt{x^2+2012}\)
\(\Leftrightarrow x^4+2x^2+1=x^2+2012\)
\(\Leftrightarrow x^4+x^2-2011=0\)
\(\Leftrightarrow x=\pm\sqrt{\dfrac{-1+\sqrt{8045}}{2}}\)